Short Term Efficacy of Ectropion Management Using Plasma Assisted Non-Invasive Surgery (PANIS) - Eghtedari , Shima; Nejat, Farhad (Journal of Ophthalmic and Optometric Sciences, 2023)
Purpose: To investigate the feasibility of using the Plasma-Assisted Non-Invasive Surgery (PANIS) technique for managing ectropion in an office-based setting. Patients and Methods: Ectropion was treated in six eyes of six patients using local anesthesia and the PANIS technique, performed in an office setting with the assistance of a slit-lamp. Plasma spots were generated using the PLEXR PLUS device (GMV Srl, Rome, Italy) to sublimate the palpebral conjunctiva by pulling the lower eyelid outward. Treatments were conducted in two sessions spaced one month apart. Visual parameters, dry eye tests, Ocular Surface Disease Index (OSDI) questionnaire results, and patient satisfaction were evaluated before and six months after the second PANIS session. Results: The study included six patients (2 females and 4 males) with a mean age of 70.17 years. Uncorrected Visual Acuity (UCVA) improved by one line in four cases. Best Corrected Visual Acuity (BCVA) showed improvement in two patients after six months. Changes in Intraocular Pressure (IOP) were not significant. The mean improvement in Tear Meniscus Height (TMH) was 0.085 mm. In terms of ectropion grade improvement, two cases showed a three-grade improvement, three cases showed a one-grade improvement, and one case showed a two-grade improvement. No patients required further surgical treatment. Conclusion: The PANIS method might offer a minimally invasive office-based procedure for both cosmetic and functional treatment of ectropion. Future studies with a higher number of participants and longer follow-up duration, are needed to provide more data regarding the long-term results of this method and its safety profile.